Percutaneous No-Scalpel Vasectomy via One Puncture in China - Li, Liping; Shao, Jialiang; Wang, Xiang (Urology Journal, 2014)
Abstract Purpose: To evaluate the efficacy and postoperative morbidity of percutaneous no-scalpel vasectomy (NSV) via one puncture in China. Materials and Methods: A total of 150 men visiting outpatient clinic of the surgery department of urology, Huashan Hospital and its Baoshan branch of Fudan University, opted for percutaneous NSV with local anesthesia. The clinical data of 150 who underwent modified NSV (MNSV) were retrospectively compared with those of 120 patients who underwent standard NSV (SNSV). The results and follow-up were recorded. Results: The reviewed average operative time was 9.8 min (range 8 to 20 min). Average incisional length was 5 mm (range 4 to 8 mm). Patients reported complete recovery in an average of 8.5 days (range 4 to 14 days). The complication rates were extremely low with this modified technique. Only one case of late healed incision was observed (0.67%). Conclusion: Percutaneous NSV via one puncture was proved to be a painless and effective form of permanent contraception with an extremely low complication rate.